Electric circuits - Nilsson, James W. (Pearson, 2015)
Designed for use in a one or two-semester Introductory Circuit Analysis or Circuit Theory Course taught in Electrical or Computer Engineering Departments Electric Circuits 10/e is the most widely used introductory circuits textbook of the past 25 years. As this book has evolved to meet the changing learning styles of students, the underlying teaching approaches and philosophies remain unchanged. MasteringEngineering for Electric Circuits is a total learning package that is designed to improve results through personalized learning. This innovative online program emulates the instructor's office-hour environment, guiding students through engineering concepts from Electric Circuits with self-paced individualized coaching. Teaching and Learning Experience This program will provide a better teaching and learning experience-for you and your students.